2010
DOI: 10.1007/s00701-010-0627-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of postoperative early mobilization for chronic subdural hematoma in elderly patients

Abstract: The results suggest that EM after one burr-hole surgery prevents postoperative complications without increasing the risk of recurrence in CSDH patients > or =65 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…Despite these concerns, the frequency of a trauma history (head injury or fall, M:F 50% vs. 57% -the second largest risk factor) compared favourably with 56% reported by Ramachandran et al [18] in a much larger series of 647 CSDH cases. Furthermore, a history of alcohol abuse/dependence (M:F 17% vs. 16%) was also of a similar order to that reported in other studies (11-24%) [19][20][21].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite these concerns, the frequency of a trauma history (head injury or fall, M:F 50% vs. 57% -the second largest risk factor) compared favourably with 56% reported by Ramachandran et al [18] in a much larger series of 647 CSDH cases. Furthermore, a history of alcohol abuse/dependence (M:F 17% vs. 16%) was also of a similar order to that reported in other studies (11-24%) [19][20][21].…”
Section: Discussionsupporting
confidence: 78%
“…In particular, there was no significant gender difference in either a history of trauma (head injury or fall) (P = 0.37) or alcohol abuse/dependence/intoxication (P = 0.89). Indeed, frequencies for alcohol abuse/dependence of 11-24% [19][20][21] render it improbable that this risk factor alone could ever explain a 2:1 male bias. Traditional assumptions therefore appear unsound.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, the study by Nakajima et al differs fundamentally from the others in the lack of closed system drainage. Although the studies by Abouzari et al and Kurabe et al [1,45] employed similar surgical paradigms, they differ significantly in the age of the patients they examine. The mean age of patients examined by Kurabe et al [45] was 77.3 years, whereas the median age in the study by Abouzari et al [1] was 56.5 years.…”
Section: Mobilization Of Patients Following Csdh Drainagementioning
confidence: 96%
“…They found no significant differences in rates of recurrence between patients who remained recumbent for 3 days postoperatively relative to those who assumed a sitting position on the day following the operation. In the second study, Kurabe et al [45] undertook a prospective study of 182 patients aged 65 years and greater who underwent single burr-hole drainage. The incidences of complications and recurrences were compared between 91 patients who were maintained in a supine position with continuous drainage and 91 patients who were mobilized (sitting or walking) on the day of surgery, and whose drains were discontinued on the day after surgery.…”
Section: Mobilization Of Patients Following Csdh Drainagementioning
confidence: 99%
“…In a recent review article it was concluded that there were significant physical benefits associated with inpatient mobilization and no evidence for associated risk of adverse events (Kalish, Lee, & Dabney, 2013). Benefits included less pain (Augustin, de Quadros, & Sarmento-Leite, 2010), less risk of delirium (Schweickert et al, 2009) or adverse events such as deep vein thrombosis (Chandrasekaran, Ariaretnam, Tsung, & Dickison, 2009; Nakao et al, 2010), urinary tract infections (Kurabe, Ozawa, Watanabe, & Aiba, 2010; Langhorne et al, 2010) or pneumonia (Clark, Lowman, Griffin, Matthews, & Reiff, 2013; Kurabe et al, 2010), and no increase in falls (Clark et al, 2013; Fisher, Galloway, et al, 2011). Moreover, ambulation and other types of physical activity helped to prevent the all too common functional decline noted in older hospitalized patients (Cumming et al, 2011; Langhorne et al, 2010).…”
mentioning
confidence: 99%